INCREASING THE ACCURACY OF VIRTUAL FITTINGS FOR TYPE AND NON-COMMERCIAL BODIES USING ARTIFICIAL INTELLIGENCE IN CLO 3D SYSTEM - PhD Sheraliyeva Risolatxon Islombek qizi; Abdujalilova Umidaxon Alhamjon qizi (Bright Mind Publishing, 2025)
This scientific article explores the enhancement of virtual fitting accuracy in apparel design by integrating artificial intelligence technologies into the CLO 3D virtual modeling system. During the study, digital garment constructions were developed for both typical and non-typical female body shapes, and Fit Map and Pressure Map data were analyzed to assess garment–body interaction. A new indicator for evaluating virtual fitting accuracy was proposed. As a result, the AI-based analytical method demonstrated high consistency when compared to real measurements, achieving a matching accuracy of 87–92%.
Keywords: Typical body shape, non-typical body shape, fit map, pressure map, 3D modeling, avatar parameters, fitting accuracy, simulation algorithms, ergonomic compatibility, FAI – Fit Accuracy Index.